Smoking cessation and harm reduction: a systematic overview of ongoing, randomized controlled trials - Mara Derissen; Sebastian Scheliga; Benjamin Clemens; Delia Leiding; Knut Kröger; Hinrich Böhner; Ute Habel (BMC Psychiatry)
Abstract Background Smoking remains one of the major public health threats, necessitating substantial scientific and societal interest in further developing and implementing systematic, smoking cessation trials. This review examines ongoing randomized controlled trials (RCTs) on smoking cessation and harm reduction, focusing on adherence to German S3 guidelines for tobacco dependence and identifying areas needing further research and neglected aspects in the implementation of treatment guidelines for tobacco dependence. Methods A systematic search was conducted on the International Clinical Trials Registry Platform, comprising multiple trial registries worldwide, to identify ongoing RCTs focusing on smoking cessation and harm reduction. Utilizing the PICOS-scheme, we focused on trials targeting the general population, with biochemical verification, psychological counseling, telemedicine, and nicotine replacement therapy /smoking cessation medication or electronic nicotine delivery systems. Exclusion criteria included trials marked as "completed," "terminated," "unknown," or "withdrawn.". Results The review identified 30 ongoing RCTs, with a majority located in North America. A significant number of trials focus on socioeconomically disadvantaged or uninsured populations, while few address cancer survivors or individuals with smoking-related diseases. Nicotine replacement therapy or smoking cessation medication is consistently used across trials, but with varying regimens. Psychotherapeutic interventions are employed in 22 trials, with motivational interviewing being the most common method. Only four trials utilize electronic nicotine delivery systems as a harm reduction strategy. The lack of standardized reporting in trial registries was a significant barrier to synthesizing and categorizing information. Geographic representation is predominantly in North America, suggesting a need for more diverse trial locations. Conclusions There is a critical need for more RCTs involving electronic nicotine delivery systems and tailored psychotherapeutic interventions. Expanding trial locations beyond North America and standardizing trial reporting could enhance the global applicability of smoking cessation strategies. Future research should focus on the long-term risks and benefits of electronic nicotine delivery systems, particularly in high-risk populations. This approach will aid in developing more effective and culturally relevant smoking cessation guidelines.